A meta-analysis of unemployment risk factors for middle-aged workers - Shiri, Rahman; Poutanen, Joonas; Härmä, Mikko; Ervasti, Jenni; Haukka, Eija (Scandinavian Journal of Work, Environment & Health, 2025)
' ' OBJECTIVE ': 'This systematic review and meta-analysis aimed to identify risk factors for unemployment among middle-aged workers. ' ' METHODS ': 'Searches were carried out in PubMed, Web of Science and Google Scholar until November 2024, focusing on observational longitudinal studies that involved workers aged 40–64 years. Three reviewers evaluated the quality of the studies. A random-effects meta-analysis was employed, and heterogeneity and publication bias were assessed. ' ' RESULTS ': 'Out of 10 432 reports, 19 longitudinal studies (N=374 585 participants) were included in the review. The meta-analysis identified multiple risk factors associated with unemployment, including suboptimal self-rated general health [hazard ratio (HR) 1.44, 95% confidence interval (CI) 1.21–1.70], mental health conditions [HR 1.48, 95% CI 1.30–1.68, particularly depressive symptoms (HR 1.42, 95% CI 1.14–1.76)], low job control (HR 1.30, 95% CI 1.17–1.43), and lack of physical activity (HR 1.56, 95% CI 1.13–2.15). Additionally, a higher risk of unemployment was observed among individuals with ≤12 years of education (HR 1.17, 95% CI 1.00–1.36), those who are unmarried, separated, or widowed (HR 1.43, 95% CI 1.14–1.79), and immigrants (HR 1.26, 95% CI 1.11–1.44). Age, gender, smoking, alcohol consumption, musculoskeletal disorders, cardiovascular and respiratory diseases, digestive diseases, diabetes, neoplasm, and limitations in daily activities did not increase unemployment risk. ' ' CONCLUSIONS ': 'This meta-analysis highlights the impact of mental health conditions, low job control, and lack of leisure-time physical activity on unemployment risk among middle-aged workers. Interventions aimed at improving mental health and increasing job control and physical activity could reduce unemployment risk.
Keywords: depression; employment; exercise; job control; mental health; meta-analysis; middle-aged worker; risk; risk factor; unemployment